2009
DOI: 10.1644/08-mamm-a-130.1
|View full text |Cite
|
Sign up to set email alerts
|

North Pacific Climate Mediates Offspring Sex Ratio in Northern Elephant Seals

Abstract: Determinants of sex ratios in animal populations have been of general interest to ecologists for decades. We tested the hypothesis that offspring sex ratio in a population of northern elephant seals (Mirounga angustirostris) was related to large-scale environmental indices reflecting ocean climate and productivity that affected the condition of reproductive females over 31 years . More males were produced during years of weaker pressure differences and warmer sea surface temperature anomalies in the northeaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
1
12
2
Order By: Relevance
“…2002, 2004; Wang 2005; Cotton & Wedekind 2008; Grubler et al. 2008; Lee & Sydeman 2009). Global temperature change has received particular attention in this context, as it is expected to alter the sex ratios of species with TSD (Nelson et al.…”
Section: Sex Ratio Biased By Esrmentioning
confidence: 99%
See 1 more Smart Citation
“…2002, 2004; Wang 2005; Cotton & Wedekind 2008; Grubler et al. 2008; Lee & Sydeman 2009). Global temperature change has received particular attention in this context, as it is expected to alter the sex ratios of species with TSD (Nelson et al.…”
Section: Sex Ratio Biased By Esrmentioning
confidence: 99%
“…2002; Schwanz & Janzen 2008; Hulin et al. 2009; Lee & Sydeman 2009; Zhang et al. 2009) or with temperature‐induced sex reversal (Wedekind et al.…”
Section: Sex Ratio Biased By Esrmentioning
confidence: 99%
“…2003, Blanchard et al. 2005, Lee & Sydeman 2009), as well as the potential for good‐condition mothers to value female‐biased sex allocation (Hewison & Gaillard 1999, Hewison et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, better maternal condition, higher maternal rank, greater maternal age and greater competition with daughters have long been examined as potential correlates of male-biased sex ratio (Myers 1978, Perret 1990, Hiraiwa-Hasegawa 1993, Hewison & Gaillard 1999, Saltz 2001, Cockburn et al 2002, Hewison et al 2002, Saltz & Kotler 2003. More recently, the complicating effects of population density and climate on maternal traits have become apparent (Kruuk et al 1999, Bradshaw et al 2003, Blanchard et al 2005, Lee & Sydeman 2009), as well as the potential for good-condition mothers to value female-biased sex allocation (Hewison & Gaillard 1999, Hewison et al 2005). In addition, correlative studies are common in mammals, yet can be limited in the ability to measure appropriate maternal traits at a relevant time during reproduction (Cameron 2004, Sheldon & West 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The diving pattern of elephant seals suggests that the sexes consume different prey (Le Boeuf 1994, Le Boeuf et al 2000. To the extent that this is so, competition for prey is predominantly intrasexual (Lee & Sydeman 2009), owing to spatial and temporal separation at sea. The reduced diving capacity of juveniles relative to adults (Le Boeuf et al 1996), as well as the rapid development of differences in foraging strategies (Le Boeuf et al 1993), has been observed during the first 2 yr of life (Le Boeuf et al 1996).…”
mentioning
confidence: 99%